Oxford guide to treaties - Hollis, Duncan B., 1970- (Oxford, U.K. : Oxford University Press, 2012)
From trade relations to greenhouse gases, from shipwrecks to cybercrime, treaties structure the rights and obligations of states, international organizations, and individuals. For centuries, treaties have regulated relations among nation states. Today, they are the dominant source of international law. Thus, being adept with treaties and international agreements is an indispensable skill for anyone engaged in international relations, including international lawyers, diplomats, international organization officials, and representatives of non-governmental organizations. The Oxford Guide to Treaties provides a comprehensive guide to treaties, shedding light on the rules and practices surrounding the making, interpretation, and operation of these instruments. Leading experts provide essays designed to introduce the law of treaties and offer practical insights into how treaties actually work. Foundational issues are covered, including what treaties are and when they should be used, alongside detailed analyses of treaty formation, application, interpretation, and exit. Special issues associated with treaties involving the European Union and other international organizations are also addressed. These scholarly treatments are complimented by a set of model treaty clauses. Real examples illustrate the approaches treaty-makers can take on topics such as entry into force, languages, reservations, and amendments. The Oxford Guide to Treaties thus provides an authoritative reference point for anyone studying or involved in the creation or interpretation of treaties or other forms of international agreement.
Introduction / Duncan B Hollis -- Defining treaties / Duncan B Hollis -- Alternatives to treaty-making : MOUs as political commitments / Anthony Aust -- Who can make treaties? : International organizations / Olufemi Elias -- Who can make treaties? : The European Union / Marise Cremona -- Who can make treaties? : Other subjects of international law / Tom Grant -- NGOs in international treaty-making / Kal Raustiala -- Making the treaty / George Korontzis -- Treaty signature / Curtis A Bradley -- Provisional application of treaties / Robert E Dalton -- Managing the process of treaty formation : depositaries and registration / Arancha Hinojal-Oyarbide and Annebeth Rosenboom -- Treaty reservations / Edward T Swaine -- The territorial application of treaties / t Domestic application of treaties / David Sloss -- State succession in respect of treaties / Gerhard Hafner and Gregor Novak -- Treaty bodies and regimes / Geir Ulfstein -- Treaty conflicts and normative fragmentation / Christopher J Borgen -- The Vienna Convention rules on treaty interpretation / Richard Gardiner -- Specialized rules of treaty interpretation : international organizations / t The validity and invalidity of treaties / Jan Klabbers -- Reacting against treaty breaches / Bruno Simma and Christian J Tams -- Exceptional circumstances and treaty commitments / Malgosia Fitzmaurice -- Terminating treaties / Laurence R Helfer -- [Sample] Treaty clauses. Initial decisions on treaty-making; Conditions on joining a treaty; Constituting the treaty and its dissemination; Applying the treaty; Amendments; The end of treaty relations.
Originally published: 2012.
Keywords: Treaties; Treaties